Economic Integration and Foreign Direct Investment: Review of Main Theoretical Concepts - Adam Marszk (Entrepreneurial Business and Economics Review)
The objective of the article is to present key theoretical relationships between economic integration and FDI flows. The research method used is a comprehensive literature review. Most influential publications, including books, articles, working papers, etc. contributing to the subject were identified. The review consists of two essential parts: theory of FDI, and theoretical relationships between economic integration and FDI flows. Finally, the outlined publications were discussed and critiqued, including the empirical context, i.e. empirical verification of the presented links.